How coach leadership behavior influences athletes’ performance: the chain-mediated role of the coach-athlete relationship and psychological fatigue - Liu, Rui; Wang, Shanshan; Li, Jun (Frontiers in Psychology, 2025)
ObjectiveAthletes’ psychological quality and competitive level are deeply influenced by coaches’ leadership behavior. It is of far-reaching significance to systematically investigate the relationship between them for carrying out scientific training and improving athletes’ competitive level. This study aims to investigate the relationships among coach leadership behavior, the coach-athlete relationship, psychological fatigue, and athletes’ performance, providing insights into enhancing athletes’ sports performance.MethodsUsing simple random sampling, 556 athletes (44.60% female) were recruited from professional training teams in the Xinjiang and Shanxi provinces of China as the study sample. The sample includes 47 s-class national athletes, 276 first-class national athletes, 171 master-class athletes, and 62 international-level athletes. Data were collected through offline surveys using the Coach Leadership Behavior Scale, the Tennis Performance Scale, the Coach-Athlete Relationship Questionnaire, and the Athlete Psychological Fatigue Questionnaire.ResultsDemocratic leadership behavior, autocratic leadership behavior, training and instruction behavior, social support behavior, and positive feedback behavior are positively correlated with the “coach-athlete” relationship and athlete performance, and negatively correlated with psychological fatigue. The “coach-athlete” relationship and psychological fatigue can serve as both simple mediators and chain mediators between democratic leadership behavior, autocratic leadership behavior, training and instruction behavior, social support behavior, positive feedback behavior, and athlete performance.ConclusionThis study systematically explored the complex relationships among coach leadership behavior, the coach-athlete relationship, psychological fatigue, and athletes’ sports performance. The findings suggest that positive coach leadership behavior may contribute to the development of athletes’ performance. Furthermore, the study underscores the significance of the coach-athlete relationship and psychological fatigue as key mechanisms through which coach leadership behavior influences athletes’ sports performance.